1991
DOI: 10.1038/349418a0
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor agonists selectively block N-type calcium channels in hippocampal neurons

Abstract: The modulation of voltage-dependent calcium channels by various neurotransmitters has been demonstrated in many neurons. Because of the critical role of Ca2+ in transmitter release and, more generally, in transmembrane signalling, this modulation has important functional implications. Hippocampal neurons possess low-threshold (T-type) Ca2+ channels and both L- and N-type high voltage-activated Ca2+ channels. N-type Ca2+ channels are blocked selectively by omega-conotoxin and adenosine. These substances both bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
1
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 26 publications
4
17
1
1
Order By: Relevance
“…Furthermore, NMDA generated inward current but had no significant effect on synaptic transmission. These findings are similar to those found in hippocampal culture (Forsythe & Clements, 1990) (Chernevskaya, Obukhov & Krishtal, 1991) (Harris & Cotman, 1983;Cotman et al 1986;Forsythe & Clements, 1990).…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, NMDA generated inward current but had no significant effect on synaptic transmission. These findings are similar to those found in hippocampal culture (Forsythe & Clements, 1990) (Chernevskaya, Obukhov & Krishtal, 1991) (Harris & Cotman, 1983;Cotman et al 1986;Forsythe & Clements, 1990).…”
Section: Discussionsupporting
confidence: 81%
“…These data suggest that NMDA receptors play a role in the regulation of GABAergic transmission. Overall, these data are consistent with previous demonstrations that presynaptic NMDA receptors contribute to NMDA-mediated phenomena in other regions of the nervous system (58)(59)(60)(61)(62)(63)(64).…”
supporting
confidence: 82%
“…While we have observed that NMDA elicits an increase in Ca2+ channel activity in CA1 pyramidal neurons, it was recently reported that NMDA receptor agonists reduced a portion of the macroscopic Ca2" current in CA1 pyramidal neurons isolated from young rats (37). In that study, however, the neurons were dialyzed with cAMP, ATP, and GTP, which would have occluded any NMDA-mediated increases in cAMP and subsequent changes in Ca2+ channel activity.…”
Section: Discussionmentioning
confidence: 89%